2014
DOI: 10.1093/cvr/cvu022
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles and exosomes for intracardiac communication

Abstract: The heart is an organ with a complex mixture of well-organized interactions of different cell types that facilitate proper myocardial contractility, sufficient perfusion, balanced myocardial extracellular stiffness, and controlled functioning of the immune system. Several cell types, including cardiomyocytes, endothelial cells, smooth muscle cells, fibroblasts, immune cells, and cardiac-derived stem cells, need a well-controlled communication system to use the complex orchestra of signalling molecules. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
204
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(206 citation statements)
references
References 113 publications
0
204
0
2
Order By: Relevance
“…After MI, PF contains an increased number of exosomes, which are small extracellular microvesicles. These vesicles contain bioactive molecules and are important for intracellular communication and activation (60). Recent proteomic analysis by Foglio et al (59) showed that clusterin is highly enriched in exosomes of PF of patients after MI.…”
Section: Wt1 In the Infarcted Heartmentioning
confidence: 99%
“…After MI, PF contains an increased number of exosomes, which are small extracellular microvesicles. These vesicles contain bioactive molecules and are important for intracellular communication and activation (60). Recent proteomic analysis by Foglio et al (59) showed that clusterin is highly enriched in exosomes of PF of patients after MI.…”
Section: Wt1 In the Infarcted Heartmentioning
confidence: 99%
“…7,8,28) Exosome release is triggered by various stimuli. 29,30) Nonetheless, the effect of anticancer agents on in vivo exosome secretion remains to be elucidated. In the present study, treatment with DXR significantly elevated serum exosome levels, expressed as exosomal protein concentration per unit of serum, in mice at 24 h post injection (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that under different conditions, exosomes are released from cardiac cells, mediating cell-to-cell communication. [135][136][137][138] Another promising class of nanoparticles useful for miRNAs delivery is represented by virus-like particles. 139 Viruslike particles are monodisperse particles, uniform in size and shape, consisting of the virus capsid devoid of genetic material.…”
Section: Site-specific Deliverymentioning
confidence: 99%